Analisis Yuridis Terhadap Sengketa Penggunaan Merek Terkenal Pada Kasus Antara Gudang Garam dan Gudang Baru - Wardhana, Adi Pratomo Kusuma (Peneliti.net, 2024)
Legal certainty regarding the trademark dispute between Gudang Garam and Gudang Baru which is essentially similar to the Gudang Garam brand which is well known as a type of product in class 34, namely kretek cigarettes. The problems discussed in this research are how legal certainty is regarding the criteria for famous brands and the basic similarities of well-known trademarks in terms of the applicable laws and regulations, what legal efforts are taken by famous brand owners to obtain legal protection for violations of basic similarities, What is ithe legal certainty regarding the protection of well-known trademarks in the Gudang Garam and Gudang Baru trademark dispute. The criteria for determining the similarity of the main elements in a brand in Article 21 paragraph (2) letter a of Law Number 20 of 2016 concerning Trademarks and Geographical Indications are the similarity of images, sounds, names, words, letters, numbers, composition. color or a combination of these elements, whether for similar or dissimilar goods or services based on general public knowledge, brand reputation obtained due to large-scale promotion, and accompanied by proof of registration of the mark in several countries. Legal consequences if a mark is proven to be substantially similar or have overall similarities, then the consequence of what the idefendant did to the plaintiff's mark is that the mark can be canceled and the registration removed. Apart from that, the plaintiff can file a claim for compensation in the form of material compensation and immaterial compensation filed by the brand owner who feels that his rights have been harmed by a party who does not have rights in using his brand. Thus, resulting in the end of ilegal protection for the brand in question.